2017
DOI: 10.1177/0973801016676012
|View full text |Cite
|
Sign up to set email alerts
|

Long-memory Modelling and Forecasting of the Returns and Volatility of Exchange-traded Notes (ETNs)

Abstract: This research provides evidence in determining the predictability of exchange-traded notes (ETNs). It utilises commodity, currency and equity ETNs as data samples, and examines the performance of the three combinations of long-memory models, that is, autoregressive fractionally integrated moving average and generalised autoregressive conditional heteroskedasticity (ARFIMA-GARCH), autoregressive fractionally integrated moving average and fractionally integrated generalised autoregressive conditional heteroskeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The findings for platinum are in accordance with the fact that this metal has stable demand from industrial users, jewelers, and automotive manufacturers. Our findings for regime 1 are similar to the results Masa and Diaz [79] obtained with ARFIMA-FIGARCH models for oil. Batten [80] showed that macroeconomic factors such as financial market sentiments, monetary policy and business cycles have effects on the volatility of silver, gold, platinum and palladium.…”
Section: Ms-fiapgarch-copula Estimation Resultssupporting
confidence: 91%
“…The findings for platinum are in accordance with the fact that this metal has stable demand from industrial users, jewelers, and automotive manufacturers. Our findings for regime 1 are similar to the results Masa and Diaz [79] obtained with ARFIMA-FIGARCH models for oil. Batten [80] showed that macroeconomic factors such as financial market sentiments, monetary policy and business cycles have effects on the volatility of silver, gold, platinum and palladium.…”
Section: Ms-fiapgarch-copula Estimation Resultssupporting
confidence: 91%
“…The incomprehensiveness of literature in the area of persistence lies in the fact that the major focus of these studies is equity markets, and very few focus on other types of security viz. bonds, FX or DR markets (Malkei, 2003;Beine & Laurent, 2003;Oh, Kim & Eom, 2006;Kumar and Maheswaran, 2013;Madhavan, 2014;Anagnostidis and Emmanouilides, 2015;Ferreira & Dionisio, 2016;Sensoy & Tabak, 2016;and Masa and Diaz, 2017).…”
Section: Persistence In Financial Asset Marketsmentioning
confidence: 99%